Volatile Organic Compounds in University Study Environments and Their Association with Tear Film Stability: An Environmental Chemistry Optometry Investigation of Digital Eye Strain (The Science Post, 2026)
Digital eye strain and dry eye symptoms are increasingly prevalent among university students due to prolonged screenexposure and extended hours spent in indoor study environments. University libraries, classrooms, and computerlaboratories may also contain volatile organic compounds (VOCs) released from paints, furniture, carpets, cleaningproducts, printers, and other indoor materials, which may negatively affect ocular health. While previous studies haveseparately examined indoor air pollution and digital eye strain, limited research has investigated their combined effecton tear film stability among students. This study aims to examine the relationship between VOC exposure inuniversity study environments, tear film stability, and digital eye strain.A cross-sectional observational study will be conducted among university students aged 18–30 years who regularlyuse digital devices for academic purposes. Indoor environmental parameters, including VOC concentration, carbondioxide levels, temperature, and relative humidity, will be measured in selected university study spaces such aslibraries, classrooms, and computer labs. Participants will complete standardized questionnaires, including the OcularSurface Disease Index (OSDI) and Computer Vision Syndrome Questionnaire (CVS-Q), to assess dry eye and digitaleye strain symptoms. Tear film stability will be evaluated using Tear Break-Up Time (TBUT). Statistical analyseswill determine associations between environmental exposure and ocular outcomes.